Monitoramento de pilares em edifícios altos de concreto armado - NAHUM, Kelly Ataide Rodrigues (Universidade Federal do Pará, 2018)
The structural behavior simulated by computer programs can be very different from reality, once the adapted loading distribution (regular) is far from the real one, and this disparity becomes more significant in high buildings because of vertical and horizontal actions which contribute to the global effects of second order for columns, making accuracy in the calculation of great importance for the stability of the overall structure. In this work are presented loads for a high building simulated using the commercial software CAD/TQS and the loads from the monitoring of 7 columns that received 3 extra bars along their height in two levels before concreting. In the steel bars were set electric strain gages to measure the strains. The data acquisition was performed through 1 module “Spider” that gets and stores the read- ings. The measurements were executed in periods previously chosen until the end of the structure building, including upper reservoir. The computation loads for the columns were satisfactory when compared to the loads from the strains and characteristic mechanical properties of the materials.